Initial concentration profile influence on migration measurements from plastic packaging: A simulation study - Manzoli, José Eduardo; Rela, Paulo Roberto; Félix, Juliana Silva [UNESP]; Monteiro, Magali [UNESP] (My University, 2006)
Migration of components from plastic packaging into foodstuffs or into medicines is a very important issue, concerning public health. Using experimental techniques, like gas chromatography-mass spectrometry, these essays measure total migration and specific migration of components from plastic packaging. This work presents an explanation and applications of a numerical technique tool for this measurement, allowing the comprehension of the diffusion process and the estimate of component migration in difficult or impractical measurements. As an application example, the non-uniform influence of initial concentration profile on the migration is presented, demonstrating the necessity of this profile determination for high quality considerations on involved metrology.
Keywords: Chemical contamination; Diffusion; Migration; Packaging; Simulation; Application examples; Experimental techniques; Gas chromatography-mass spectrometry; Initial concentration; Migration measurement; Numerical techniques; Gas chromatography; Planning; Sustainable development; Units of measurement; Measurements